PENGARUH DEBT TO ASSET RATIO (DAR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP PROFITABILITAS PERUSAHAAN INDEKS LQ 45 BURSA EFEK INDONESIA - Pebrianti, Yulia (Discovery : Jurnal Ilmu Pengetahuan, 2019)
Abstract This research is aimed to test the effect of debt to asset ratio (DAR) and debt to equity ratio (DER) on return on asset (ROA). The research uses a data set consist of 45 companies listed as LQ 45 Index in 2017 period. Purposive sampling is used as sampling method. Regression analysis is used to compute the parameters. The results show that debt to asset ratio has no significant effect on return on asset, and debt to equity ratio has no significant effect too on return on asset. Key words: DAR, DER, ROA